2013
DOI: 10.1345/aph.1q483
|View full text |Cite
|
Sign up to set email alerts
|

Alteplase for the Treatment of Catheter Occlusion in Pediatric Patients

Abstract: Alteplase appears to show efficacy for treatment of thrombus-related venous catheter occlusion in pediatric patients; however, data regarding its use in occluded dialysis catheters are limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…A literature review focusing on pediatric patients with CVCs and the use of TPA revealed that 50–90% of catheters were cleared of thrombosis when TPA was instilled, with improved efficacy when doses where higher and dwell times were longer (53). Unfractionated heparin has also been used to maintain and improve catheter patency.…”
Section: Resultsmentioning
confidence: 99%
“…A literature review focusing on pediatric patients with CVCs and the use of TPA revealed that 50–90% of catheters were cleared of thrombosis when TPA was instilled, with improved efficacy when doses where higher and dwell times were longer (53). Unfractionated heparin has also been used to maintain and improve catheter patency.…”
Section: Resultsmentioning
confidence: 99%
“…When reviewing the secondary outcomes, we found no significant differences between cohorts in number of complete occlusions. This was an unexpected result because Anderson et al (2013) in their review reported that shorter times between identification of an occlusion and treatment improved CVAD patency outcomes. In the present study, the failure to find a significant difference between cohorts in number of complete occlusions may be attributed to deviations to the nurseled protocol.…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, no similar studies have been conducted to evaluate the effect of a nurse-led protocol on time to treatment of partially occluded CVADs in either adult or pediatric populations. The majority of pediatric studies (reviews and original research) focused on dose and dwell times (Anderson et al, 2013;Giordano et al, 2015;Peng et al, 2011;Soylu et al, 2010), number of instillations (Anderson et al, 2013;Peng et al, 2011), restoration of patency (Anderson et al, 2013;Blaney et al, 2006;Peng et al, 2011), and complications. (Blaney et al, 2006;Soylu et al, 2010;Ullman et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravenously, tPA is administered as a continuous rate infusion due to its short half‐life, which has been reported to be between 2 and 3 minutes and 16.6 minutes . Although tPA has a short intravascular half‐life, the effect of this drug may be more prolonged in extravascular environments (eg, within central venous catheters) . An increased percentage of partially or fully occluded central venous catheters become patent after a 120 minute dwell time compared to a 30 minute dwell time .…”
Section: Discussionmentioning
confidence: 99%